Low and high orders light scattering in particulate media - Meglinski, Igor V.; Romanov, V. P.; Churmakov, D. Y.; Berrocal, Edouard; Jermy, Mark C.; Greenhalgh, Douglas A. (Cranfield University, 2004)
We present the results of a theoretical study providing details of propagation of laser radiation within disperse randomly inhomogeneous intermediately single- to-multiple scattering media. A quantitative analysis of scattering orders in the transition from single to multiple scattering is presented. Crossed source- detector fiber optics geometry used to separate the intensity of single scattering from higher scattering orders. The results demonstrate good agreement between analytical and Monte Carlo techniques. This validates the use of the Monte Carlo approach in the intermediate single-to-multiple scattering regime. The method used can be applied to verify analytical results against experiment via the Monte Carlo calculations that include imperfections of the experiment.